Review Artikel : Evaluasi Pengobatan Obat Antihipertensi pada Pasien Hipertensi dengan atau Tanpa Komorbid pada Fasilitas Layanan Kesehatan - indah; Fevi Aristia, Bella; Laila , Alfu; Putri Nur Hidayah, Eka (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
The effectiveness of hypertension treatment is closely linked to blood pressure control. Ineffective treatment can lead to uncontrolled blood pressure, increasing the risk of serious complications, such as stroke, heart disease, and kidney failure. The rationality of treatment is an important factor that influences the effectiveness of therapy. Rational treatment, which is tailored to the patient's condition, can help achieve optimal blood pressure control and reduce the risk of complications. This review article aims to summarize and review the evaluation results of antihypertensive drug use in hypertension patients treated at healthcare facilities. The review process involved searching for relevant articles on Google Scholar using keywords such as evaluation, rationality, and hypertension treatment, published over the past 10 years. The review results showed that the evaluation of hypertension treatment should be assessed from four main aspects: right patient, right indication, right drug, and right dose. Hypertension treatment, whether with comorbidities or without, may involve single therapy or a combination of three drugs. Based on the data obtained, the majority of the treatments were rational in terms of right patient and right indication. However, there were still instances of inaccuracy, particularly in selecting the right drug and appropriate dosage. Inaccurate drug selection and dosing can reduce the effectiveness of treatment and increase the likelihood of adverse side effects. It is crucial to ensure that the therapy provided is suitable for the patient’s medical condition, with appropriate drug selection and dosage. Education on treatment rationality for healthcare professionals and patients is essential to optimize hypertension treatment outcomes. This approach will help improve hypertension management in the community and reduce the burden of complications caused by uncontrolled hypertension.